Risk analysis and portfolio modelling - David E. Allen; Elisa Luciano (Journal of Risk and Financial Management, 2019)
Financial risk measurement is a challenging task because both the types of risk and their measurement techniques evolve quickly. This book collects a number of novel contributions for the measurement of financial risk, which addresses partially explored risks or risk takers in a wide variety of empirical contexts.
Keywords: 330; portfolio analysis; risk analysis; risk attribution